Red Light-Emitting Diode Based on Blue InGaN Chip with CdTe(x)S((1 − x)) Quantum Dots - Wang, Rongfang (Nanoscale Res Lett, 2017)
Thioglycolic acid-capped CdTe(x)S((1 − x)) quantum dots (QDs) were synthesized through a one-step approach in an aqueous medium. The CdTe(x)S((1 − x)) QDs played the role of a color conversion center. The structural and luminescent properties of the obtained CdTe(x)S((1 − x)) QDs were investigated. The fabricated red light-emitting hybrid device with the CdTe(x)S((1 − x)) QDs as the phosphor and a blue InGaN chip as the excitation source showed a good luminance. The Commission Internationale de L’Eclairage coordinates of the light-emitting diode (LED) at (0.66, 0.29) demonstrated a red LED. Results showed that CdTe(x)S((1 − x)) QDs can be excited by blue or near-UV regions. This feature presents CdTe(x)S((1 − x)) QDs with an advantage over wavelength converters for LEDs.